Blockchain and Business Process Management in Health Care, Especially for COVID-19 Cases - Ibrahim Abunadi (Hindawi-Wiley, 2021)
From this global health disaster, the health profession is searching for a new technology to monitor and mitigate COVID-19 infections. Accurate and reliable data are needed to surveil and prevent the diffusion of the coronavirus. However, there is a lack of consistent data on existing technologies. Various entities—for example, medical labs and public hospitals—could provide data on patients with coronavirus infection. Yet, this information might not be precise since it is not supervised and recorded correctly. This paper proposes a Blockchain and Business Process Management (BBPM) system in healthcare to solve these problems. This system could be crucial in tracing coronavirus diffusion and discovering more dangerous patients and is extremely proficient at controlling the disease. BBPM can be utilized like a digital database that includes information concurrently utilized and distributed inside a wide, decentralized, and openly accessible network. Usage of blockchains in the medical sector is anticipated to revolutionize the industry in many regions, primarily because centralization in current health technologies inhibits information sharing and causes a lack of confidentiality. Furthermore, BBPM could help supervise the diffusion of coronavirus infection worldwide by utilizing blockchain networks on the mobile devices of individuals. Protecting patient information is one of the critical strengths of BBPM. Participating BBPM nodes can be governments, hospitals, testing labs, or patients. In addition, the digital ledger has a few documents, including patient reports, consequences, the condition of treatment, and a summary of discharge. The BBPM system is categorized into four processes. In the first process, the patient is analyzed and diagnosed by a testing lab to detect any early signs of COVID-19 infection. A sample of the patients was taken. If it is positive, the second process begins. In the second process, the patient is isolated and begins treatment for a minimum of 14 days. If the patient’s health condition is improving, the third process begins. In the third process, the patients were retested for COVID-19. If the patient sample is negative, the patient is discharged, and an outline is created. During discharge, the patient pays the hospital for treatment. However, if the patient sample is positive, the isolation period is continued for another 14 days. In the last process, the details of total COVID-19 are confirmed, recovered, and death cases are conveyed to the government by the testing labs and hospitals. Patient records are stored for upcoming usage; their confidentiality is maintained when distributed on a larger scale. BBPM can guarantee the security and accuracy of patients’ recorded data.